Deception in Caregiving: Unpacking Several Ethical Considerations in Covert Medication. Issue 2 (June 2017) - Abdool, Rosalind (Roz)
From a clinical ethics perspective, I explore several traditional arguments that deem deception as morally unacceptable. For example, it is often argued that deception robs people of their autonomy (Frankfurt 2005). Deception also unfairly manipulates others and is a breach of important trust-relations (Williams 2009, Scanlon 1998). In these kinds of cases, I argue that the same reasons commonly used against deception can provide strong reasons why deception can be extremely beneficial for patients who lack mental capacity. For example, deception can enhance, rather than impair, autonomy in certain cases. I argue that deception ought to only be used after considering several key morally relevant factors and provide a practical and morally justifiable framework for exploring these issues.